1998
DOI: 10.1016/s0378-1097(98)00126-8
|View full text |Cite
|
Sign up to set email alerts
|

The binding and utilization of hemoglobin by Prevotella intermedia

Abstract: Prevotella intermedia, a putative periodontopathic microorganism, requires iron for growth. Hemoglobin can be a major source of iron for bacterial growth in vivo since it is present in the crevicular fluid collected from periodontitis sites. Experiments studying the growth of P. intermedia in iron-depleted Todd-Hewitt broth supplemented with human hemoglobin showed that the bacteria were able to utilize human hemoglobin as a source of iron. The uptake of iron from hemoglobin by P. intermedia appears to be init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
25
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 15 publications
3
25
0
Order By: Relevance
“…The observation that globin strongly inhibited hemoglobin‐binding activity suggests that the globin moiety of the hemoglobin molecule may be essential for binding to P. nigrescens . Similar results were also documented for P. gingivalis (15) and P. intermedia (17). Duchesne et al.…”
Section: Discussionsupporting
confidence: 86%
“…The observation that globin strongly inhibited hemoglobin‐binding activity suggests that the globin moiety of the hemoglobin molecule may be essential for binding to P. nigrescens . Similar results were also documented for P. gingivalis (15) and P. intermedia (17). Duchesne et al.…”
Section: Discussionsupporting
confidence: 86%
“…The phenomenon has been noted in a group of anaerobic species that are mainly oral pathogens and were previously known as black-pigmented Bacteroides species but have now been reclassified as Porphyromonas and Prevotella species (17). These bacteria depend largely on external heme (either hemoglobin or hemopexin) to satisfy their demand for iron (20) and to a greater or lesser extent accumulate a black pigment intracellularly that consists of an iron-containing heme aggregate (e.g., hematin) together with various amounts of iron-free PPIX (28,29). If they accumulate PPIX they will be photosensitive (13), however, if they mainly have hematin they will not be photo- showed that these species were more sensitive when grown on media containing hemin as an iron source compared to hemoglobin (14).…”
Section: Discussionmentioning
confidence: 99%
“…Oral black‐pigmented anaerobes, such as Porphyromonas gingivalis and Prevotella intermedia, are putative periodontal pathogens (14, 18, 24). These bacteria have been frequently isolated from subgingival plaque in patients suffering from adult periodontitis (25).…”
mentioning
confidence: 99%